232k views
0 votes
What is

Factorise:
4x squared -1
9x squared -64
49x squared -121
4x squared -y squared
9a squared -b squared
16a squared -9b squared
x squared -42 squared

Please help me ASAP

User AlexT
by
6.1k points

2 Answers

6 votes

i am just here to troll lol

User Ramyani
by
5.3k points
4 votes

Step-by-step explanation:

There is a theorem :


\mathbf{a^(2)-b^(2)=(a-b)(a+b)}

Proof: open the brackets on right side of equality by using distributive property

RHS = a(a+b) - b(a+b)

RHS =
\mathrm{a^(2)+ab-ab-b^(2)}

RHS =
\mathrm{a^(2)-b^(2)} = LHS

Using the above theorem you can solve every question you asked:


  • \mathrm{4x^(2)-1=(2x)^(2)-1^(2)=(2x-1)(2x+1)}

  • \mathrm{9x^(2)-64=(3x)^(2)-(8)^(2)=(3x-8)(3x+8)}

  • \mathrm{49x^(2)-121=(7x)^(2)-(11)^(2)=(7x-11)(7x+11)}

  • \mathrm{4x^(2)-y^(2)=(2x)^(2)-y^(2)=(2x-y)(2x+y)}

  • \mathrm{9x^(2)-b^(2)=(3x)^(2)-b^(2)=(3x-b)(3x+b)}

  • \mathrm{16x^(2)-9b^(2)=(4x)^(2)-(3b)^(2)=(4x-3b)(4x+3b)}

  • \mathrm{x^(2)-42^(2)=(x-42)(x+42)}
User Ndonohoe
by
6.1k points